Accumulation of HT-2 toxin from contaminated mushroom compost by edible Agaricus bisporus. Issue 4 (3rd April 2022) - Varga, Emese; Soros, Csilla; Fodor, Peter; Cserháti, Mátyás; Sebők, Rózsa; Kriszt, Balázs; Geosel, Andras
Abstract: Wheat straw is commonly used as a cellulose source in mushroom compost and could be a secondary source of mycotoxin contamination in the food chain. We cultivated edible Agaricus bisporus and Pleurotus ostreatus on T-2/HT-2 artificially-contaminated mushroom compost and developed and in-house validated an UHPLC-MS/MS method for determination of T-2, HT-2, T2-triol and T2-tetraol in mushroom compost and mushroom basidiocarp. A rapid phase I metabolization of T-2 and HT-2 in mushroom compost was observed. In Agaricus bisporus, basidiocarps 8–15 µg kg −1 accumulation of HT-2 calculated on wet weight was measured. No detectable mycotoxins were found in Pleurotus ostreatus basidiocarp.